Approaching the Interpretation of Discordances in SARS-CoV-2 Testing. (23rd March 2021) - Wontakal, Sandeep N; Bortz, Robert H; Lin, Wen-Hsuan W; Gendlina, Inessa; Fox, Amy S; Hod, Eldad A; Chandran, Kartik; Prystowsky, Michael B; Weiss, Louis M; Spitalnik, Steven L
Abstract: The coronavirus disease 2019 pandemic has upended life throughout the globe. Appropriate emphasis has been placed on developing effective therapies and vaccines to curb the pandemic. While awaiting such countermeasures, mitigation efforts coupled with robust testing remain essential to controlling spread of the disease. In particular, serological testing plays a critical role in providing important diagnostic, prognostic, and therapeutic information. However, this information is only useful if the results can be accurately interpreted. This pandemic placed clinical testing laboratories and requesting physicians in a precarious position because we are actively learning about the disease and how to interpret serological results. Having developed robust assays to detect antibodies generated against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and serving the hardest-hit areas within the New York City epicenter, we found 3 types of discordances in SARS-CoV-2 test results that challenge interpretation. Using representative clinical vignettes, these interpretation dilemmas are highlighted, along with suggested approaches to resolve such cases.